3D printed iris bandpass filters for millimetre‐wave applications. Issue 22 (7th October 2015) - Zhang, B.; Zirath, H.
Abstract : Two iris bandpass filters implemented by three‐dimensional (3D) printing technology for millimetre‐wave applications are demonstrated for the first time. The filters are designed at the E‐band (60–90 GHz), and fabricated by selective laser melting using CuSn15 alloy powder. A shifted passband and increased insertion loss are observed, which is caused by the fabrication tolerance of dimensional control and surface roughness. Methods to compensate the fabrication tolerance are proposed and the design procedures are provided. The presented results prove the great potential of 3D printing technology for millimetre wave applications.